2018
DOI: 10.1029/2018ja025228
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Seismogenic Electric Currents Through the Earth's Atmosphere

Abstract: Seismogenic models have been recently proposed to explain precursors before earthquakes occurrences. Those models refer to physical processes linking the lithosphere, the atmosphere, and the ionosphere. We analyze in this work the curl-free current model describing the current flow from the lithosphere to the ionosphere through the atmosphere. We use a numerical simulation based on the finite element method to derive the current between the ground and the ionosphere. We have shown that the curl-free approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…We notice that several papers have already ruled out the electrostatic hypothesis (see a discussion in Sorokin et al, 2015). Especially in the papers on the critical analysis of the electrostatic channel by Denisenko (2015) and Denisenko et al (2018), they have calculated the penetrations of lithospheric electric field and current into the ionosphere and concluded that the penetrating electric field and current in the ionosphere are negligible. They further suggest that other atmospheric processes such as AGWs should be considered to explain the lithospheric influence on the ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…We notice that several papers have already ruled out the electrostatic hypothesis (see a discussion in Sorokin et al, 2015). Especially in the papers on the critical analysis of the electrostatic channel by Denisenko (2015) and Denisenko et al (2018), they have calculated the penetrations of lithospheric electric field and current into the ionosphere and concluded that the penetrating electric field and current in the ionosphere are negligible. They further suggest that other atmospheric processes such as AGWs should be considered to explain the lithospheric influence on the ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…A further introduction to these hypotheses can be found in [ 2 , 22 ]. A series of critical studies [ 23 , 24 , 25 , 26 ] has pointed out that the electric field/current, as proposed in the first chemical and the third electrostatic channel is weak, and that the penetration from the lithosphere into the ionosphere is negligible. Additionally, as compared with the first chemical and the third electrostatic channel, much observational evidence has been mainly accumulated in the subionospheric VLF/LF data to support the second AGW hypothesis [ 12 ], and thus we think that the AGW channel is the most promising candidate as the LAIC mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the electromagnetic channel, difficulties are encountered in simulation of the penetrating electric field and current through the atmosphere. Models [60][61][62] show that the field penetrating into the ionosphere is several orders of magnitude smaller than required. The mechanism based on gravity waves [13] cannot be discarded as well.…”
Section: Discussionmentioning
confidence: 97%